PELATIHAN TEKNIK BERMAIN BADMINTON PADA SISWA SD: PELATIHAN TEKNIK BERMAIN BADMINTON PADA SISWA SD - Dwi Cahyati Anggraeni (CV SWA Anugerah, 2023)
Community service is a tridarma of higher education that must be carried out by every lecturer and student within the university to maintain existence as a higher education citizen. This community service develops techniques for playing badminton, especially for elementary school students in Banyuputih Village, Kidul Kec. Jatiroto Lumajang in adding insight into the technique of playing Badminton during PPKM. Badminton Playing Technique Training especially for elementary school students by paying attention to the ability of elementary school children in Banyuputih Kidul Village which is very lacking so training needs to be done. This community service activity is running smoothly so there will be follow-up service with the same theme so that this activity can be maintained in the continuity of the choice of Banyuputih Kidul Village, because it saw the participation of elementary school children who were very enthusiastic about participating in the training